Evidence that Orai1 does not contribute to store-operated TRPC1 channels in vascular smooth muscle cells - Shi, Jian (2017)
Ca2+-permeable store-operated channels (SOCs) mediate Ca2+ entry pathways which are involved in many cellular functions such as contraction, growth, and proliferation. Prototypical SOCs are formed of Orai1 proteins and are activated by the endo/sarcoplasmic reticulum Ca2+ sensor stromal interaction molecule 1 (STIM1). There is considerable debate about whether canonical transient receptor potential 1 (TRPC1) proteins also form store-operated channels (SOCs), and if they do, is Orai1 involved. We recently showed that stimulation of TRPC1-based SOCs involves store depletion inducing STIM1-evoked Gαq/PLCβ1 activity in contractile vascular smooth muscle cells (VSMCs). Therefore the present work investigates the role of Orai1 in activation of TRPC1-based SOCs in freshly isolated mesenteric artery VSMCs from wild-type (WT) and Orai1−/− mice. Store-operated whole-cell and single channel currents recorded from WT and Orai1−/− VSMCs had similar properties, with relatively linear current-voltage relationships, reversal potentials of about +20mV, unitary conductances of about 2pS, and inhibition by anti-TRPC1 and anti-STIM1 antibodies. In Orai1−/− VSMCs, store depletion induced PLCβ1 activity measured with the fluorescent phosphatidylinositol 4,5-bisphosphate/inositol 1,4,5-trisphosphate biosensor GFP-PLCδ1-PH, which was prevented by knockdown of STIM1. In addition, in Orai1−/− VSMCs, store depletion induced translocation of STIM1 from within the cell to the plasma membrane where it formed STIM1-TRPC1 interactions at discrete puncta-like sites. These findings indicate that activation of TRPC1-based SOCs through a STIM1-activated PLCβ1 pathway are likely to occur independently of Orai1 proteins, providing evidence that TRPC1 channels form genuine SOCs in VSMCs with a contractile phenotype.